Paaloka sebagai Ekspresi Budaya Religius Masyarakat Detunggali - Fransiskus Saverius Minggu; Yulianus Kian; Jefrianus Ulu Manek; Paskalis Jhon Juang; Frederikus rifaldo Soro; Robertho Mario Wetan Kwure (Pusat Riset dan Inovasi Nasional, 2026)
Paaloka is a religious–cultural practice of the indigenous community of Detunggali Lewumbangga Village that functions as a medium for maintaining relationships with ancestors as well as a means of fostering social solidarity. This study aims to analyze the religious meaning of Paaloka and its relevance from the perspective of Catholic faith and within the local social context. The research employs a descriptive qualitative method, with data collected through observation and in-depth interviews with traditional leaders, church leaders, and community members. Data analysis was conducted through processes of reduction, categorization, and thematic interpretation. The findings indicate that Paaloka embodies religious values such as expressions of gratitude, petitions for blessings, and respect for ancestors, and serves to strengthen communal identity and social cohesion. From a theological perspective, Paaloka can be understood as a space for the inculturation of Catholic faith insofar as it is interpreted as an expression of prayer and lived faith in God without negating the teachings of the Church. This study underscores the importance of dialogue between faith and culture in the development of contextual pastoral practice.